Perancangan Prototype UI/UX Pada Pelacak Kendaraan Operasional Dengan Menggunakan Metode Design Thinking (Studi Kasus Penerapan Pada Instansi BUMN) - Billan, Angel Caroline; Dedy Kurniawan; Ahmad Rifai; Putri Eka Sevtiyuni; Allsela Meiriza (STMIK Budi Darma, 2024)
Delivery of information and presentation of data can be delivered through applications that are implemented to help create a system based on company needs. This problem occurs because the government has more than 400,000 applications and each ministry/institution has around 24,000 applications. Many applications in companies do not operate multifunctionally because they are considered to be inconvenient and inefficient to use, thus causing the applications to become unused in companies. To develop a new system that will be implemented in a company, of course you want the application to be used continuously by users. One way to correct this error is to create a good UI/UX that can be adopted by the company by involving a deep understanding of the user and organizational goals. The resulting solution to overcome this problem was a UI/UX design at PT. Pertamina Hulu Rokan Regional 1 Zone 4 Field Limau which was designed in the form of a design prototype using the design thinking method. The main goal of making a UI/UX prototype is to improve the user experience at the company by meeting the company's needs for designing operational vehicle tracking applications. The final results of this research use the design thinking method and user experience questionnaire (UEQ) as testing to determine whether the response tends to be positive or negative from users. The results of the trial on the prototype received an